Efficacy and Safety of an Aflibercept Treat-and-Extend Regimen in Treatment-Naïve Patients with Macular Oedema Secondary to Central Retinal Vein Occlusion (CRVO): A Prospective 12-Month, Single-Arm, Multicentre Trial - Jose Garcia-Arumi; Francisco Gómez-Ulla; Navea Amparo; Enrique Cervera; Alex Fonollosa; Luis Arias; Javier Araiz; Juan Donate; Marta Suárez de Figueroa; Lucia Manzanas; Jaume Crespí; Roberto Gallego (Journal of Ophthalmology)
Objectives. To evaluate efficacy and safety of an aflibercept treat-and-extend (TAE) regimen in patients with macular oedema (MO) secondary to central retinal vein occlusion (CRVO). Design, Setting, and Patients. Phase IV, prospective, open-label, single-arm trial in 11 Spanish hospitals. Treatment-naïve patients with <6 month diagnosis of MO secondary to CRVO and best-corrected visual acuity (BCVA) of 73-24 ETDRS letters were included between 23 January 2015 and 17 March 2016. Intervention. Intravitreal aflibercept 2 mg monthly (3 months) followed by proactive individualized dosing. Main Outcomes. Mean change in BCVA after 12 months. Results. 24 eyes (24 patients) were included; mean (SD) age: 62.8 (15.0) years; 54.2% male; median (IQR) time since diagnosis: 7.6 (3.0, 15.2) days. Mean BCVA scores significantly improved between baseline (56.0 (16.5)) and Month 12 (74.1 (17.6)); mean (95% CI) change: 14.8 (8.2, 21.4); P=0.0001. Twelve (50.0%) patients gained ≥15 ETDRS letters. Foveal thickness improved between baseline (mean: 569.4 (216.8) µm) and Month 12 (mean 257.4 (48.4) µm); P<0.0001. At Month 12, 8.3% patients had MO. The mean (SD) number of injections: 8.3 (3.0). No treatment-related AEs were reported. Five (20.8%) patients experienced ocular AEs. Two nonocular serious AEs were reported. Conclusions. An aflibercept TAE regimen improves visual acuity in patients with MO secondary to CRVO over 12 months with good tolerability.